Lecture Notes in Real-Time Intelligent Systems - Mizera-Pietraszko, Jolanta; Pichappan, Pit.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Intelligent computing refers greatly to artificial intelligence with the aim at making computer to act as a human. This newly developed area of real-time intelligent computing integrates the aspect of dynamic environments with the human intelligence. This book presents a comprehensive practical and easy to read account which describes current state-of-the art in designing and implementing real-time intelligent computing to robotics, alert systems, IoT, remote access control, multi-agent systems, networking, mobile smart systems, crowd sourcing, broadband systems, cloud computing, streaming data and many other applications areas. The solutions discussed in this book will encourage the researchers and IT professional to put the methods into their practice.  .
A Research on Classroom Teaching Ability System Construction of English Teachers combined with Artificial Intelligence -- Research on Education and Teaching Resources Management System based on ASP.NET -- Service Outsourcing Oriented Language Computer Model to Build Innovative Personnel Training -- Analysis and System Simulation of Flight Vehicle Sliding Mode Control Algorithm Based on PID Neural Network -- Multi Controller Software Defined Network Link Fault Location based on Tree Decomposition Method -- A New Model for Analyzing the Win Probability and Strength of the Two Sides of the Table Tennis Match -- Damping Loss Prevention on Aerobics Special Shoe Materials based on Intelligent Analysis -- Intelligent Agricultural Machinery Monitoring System Based on the Cloud -- Research on the Operation of Electric Intelligent Automation Based on Computational Intelligence -- Improvements of Wireless Network Routing Clustering Algorithm -- Research on Personalized Recommendation of Electronic Commerce Website Based on Text Mining -- Analysis on the Application of Artificial Intelligence Technology in the Construction of the Internet Interactive Platform of Inquiry Curriculum.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence